Preoperative Serum Prealbumin Level and Adverse Prognosis in Patients With Hepatocellular Carcinoma After Hepatectomy: A Meta-Analysis - Fan, Yu; Sun, Yimeng; Man, Changfeng; Lang, Yakun (Frontiers in Oncology, 2021)
Background: Prealbumin is a sensitive indicator of liver function and nutritional status. Objectives: This meta-analysis aimed to examine the association of serum prealbumin level with the prognosis of patients with hepatocellular carcinoma (HCC) undergoing hepatectomy. Methods: We comprehensively searched the PubMed, Embase, Wanfang, CNKI, and SinoMed databases up to September 1, 2021. Eligible studies should report the association of serum prealbumin level with prognosis and provide the multivariable-adjusted risk estimate of outcomes of interest in HCC patients undergoing hepatectomy. Results: A total of 11 studies with 7442 HCC patients were identified and analyzed. A fixed-effect model meta-analysis showed that low serum prealbumin level was associated with poor overall survival (hazard ratio [HR] 1.54; 95% confidence interval [CI] 1.42–1.68), recurrence-free survival (HR 1.34; 95% CI 1.17–1.52), and higher risk of postoperative hepatic insufficiency (HR 2.21; 95% CI 1.36–3.60) in HCC patients. Sensitivity and subgroup analyses confirmed the robustness of low serum prealbumin in predicting poor overall survival. Conclusions: This meta-analysis indicated that low preoperative serum prealbumin level was significantly associated with adverse prognosis in HCC patients undergoing hepatectomy.